Efeitos nefrotóxicos do veneno de Bothrops jararaca e estado da ação de antagonistas do PAF e da cicloxigenase no rim perfundido de rato - Monteiro, Helena Serra Azul (1990)
Wephrotoxic Activitf ©f B&tAmjps jnaua Veaom aad th® Effect® of PAF ÂntagoBists and C^cloo^yfenase Inibitors in tbe Rat Perfased Kidneys. Helena Serra Azul Monteiro UNICAMP/UFC, 1990. This work evaluates nephrotoxic effects of the venom of Botimps jararaca , a snake responsible for many snake bite accidents in the Northeast of Brazil and thus is an important public health problem in our country. The model used was the isolated perfased rat kidney. We used a modified Krebs-Henseleit solution with added albumin at 6g% which produced more reliable than albumin concentrations of 2 and 4g%. The parameters studied were: perfusion pressure (PP), renal vascular resístance (RVR), urinary flow (UF), glomerular filtration rate (GFR), sodium transport (TNa+), potassium transport (TK+), free water dearan.ce (CHgO), proximal transport of sodium (pTNa+) and distai transport of sodium (dTNa+). The results for the control group were: PP»149,17 ± 4,03 mmHg, RVR®6,38 ± 0,68 mmHg/mlAgAminA UF«0,26 ± 0,005 mlAgAminA GFR=1,13 ± 0,21 mlAgAminA TNa+= 136,13 ± 28,68 uEq.gAminA %TNa+«78,53± 1,91. In the kidneys treated by the venom (lOmgfrnl) we observed, at 30 min of perfusion, a marked decrease in these parameters: PP=100,50 ± 10,81 mmHg.ml' KgAmind (45%); RVR=3,92 ± 0,47 mmHg/mlAgAmin'Í (31,10%); UF»0,02 ± 0,05 mlAgAmin-1 (85%), GFR-0,06 + 0,02 mlAgAmin "1 (90%); TNa^-5,30 ± 2,73piEq.gAmin'l (90%). In an attempt to block these toxic effects we have used BN 52021 and WEB 2086, two drugs which are platelet activating factor (PAF) antagonists. BN 52021 did not protect against the toxic effects of the venom, except in blocking the decrease in sodium and potassium in the tissues. WEB 2086 blocked the urinary flow and GFR changes by the venom and even elevated these parameters in relation to the Controls. The perfusion pressure was not reversed. CHgO, dTNa+ and %dTNa+ all presented negative values when compared to Controls. We also found that indomethacin antagonized the toxic effects of the venom found in UF, GFR, RVR, and partially blocked PP. The venom also produced a decrease in tissue Na+ and K+, which in tum was blocked by BN 52021, WEB 2086 and indomethacin. Histopathological study revealed that in both groups, treated and untreated by the venom, there was a tabular dilatation and tumefaction. These effects could be the result of the perfusion itself. However, in the groups treated -viii- IfffíiTO with the venom we found peater amounts of protein inside the tabules and in the ^omeralar spaces. We also found a tabular necrosis in two kidneys. With this technique we nowhave a model to stady nepbrotwdc dnçs. We conciude that the venom produces significant alterations of UF, GFR, RVR, PP, TNa4; %TNa+ and %TK.4', with a decrease in leveis oftissue Na+ and K+.